2022
DOI: 10.3390/v14122690
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Released by Influenza-Virus-Infected Cells Carry Factors Capable of Suppressing Immune Defense Genes in Naïve Cells

Abstract: Exosomes are involved in intercellular communication and can transfer regulatory molecules between cells. Consequently, they can participate in host immune response regulation. For the influenza A virus (IAV), there is very limited information on changes in exosome composition during cell infection shedding light on the potential role of these extracellular membrane vesicles. Thus, the aim of our work was to study changes in exosomal composition following IAV infection of cells, as well as to evaluate their ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Inhibition of FPR2 in experimental H1N1 infection decreased the production of IL‐6 and IFN‐ β in BAL fluid, decreased viral titres and decreased lethality rates associated with infection (Tcherniuk et al, 2016). Recent findings indicate that IAV infection stimulates the release of exosomes that down‐regulate several genes involved in the inflammatory response, including the AnxA1 gene (Zabrodskaya et al, 2022). Additionally, in vitro studies have demonstrated that H1N1 infection up‐regulates the expression of FPR2 (Ampomah et al, 2018), likely as a strategy to promote disease progression.…”
Section: Annexin A1 (Anxa1)mentioning
confidence: 99%
“…Inhibition of FPR2 in experimental H1N1 infection decreased the production of IL‐6 and IFN‐ β in BAL fluid, decreased viral titres and decreased lethality rates associated with infection (Tcherniuk et al, 2016). Recent findings indicate that IAV infection stimulates the release of exosomes that down‐regulate several genes involved in the inflammatory response, including the AnxA1 gene (Zabrodskaya et al, 2022). Additionally, in vitro studies have demonstrated that H1N1 infection up‐regulates the expression of FPR2 (Ampomah et al, 2018), likely as a strategy to promote disease progression.…”
Section: Annexin A1 (Anxa1)mentioning
confidence: 99%
“…RNAs: miRNA composition (miR-21-3p, miR-26a-5p, miR-23a-5p, miR-548c-5p) and mRNA composition (RPL13A, MKNK2 and TRIB3) (Zabrodskaya et al, 2022);…”
Section: Influenza a Virus (Iav) Respiratory Tract Diseasementioning
confidence: 99%
“…•Suppressing immune defense genes: EVs from IAV-infected cells reduce the immune response of neighbouring intact cells, leading to more effective IAV replication (Zabrodskaya et al, 2022). •Promoting M1 polarization and recruitment of macrophages: EVs from the supernatant of IAV-infected cells promote the recruitment and polarization of peritoneal M1 macrophages .…”
Section: Influenza a Virus (Iav) Respiratory Tract Diseasementioning
confidence: 99%
“…For example, miR-mRNA interactions predicted to decrease gene expression by degradation of mRNA should reflect this in both attenuated mRNA transcript levels and reduced protein output [70]. Furthermore, researchers may consider expanding on the local or systemic effects of viral miRNA packaged into exosomes and virus-induced changes in exosomal host miRNA levels [10,83,103]. They should also critically evaluate if changes in host miRNA levels are due to viral manipulation or if they are a potential defensive response to infection.…”
Section: Pro-viral Mirna Regulation Of Viral Infectionmentioning
confidence: 99%